2019
DOI: 10.4028/www.scientific.net/amm.895.45
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Calotropis Procera Natural Fiber Reinforced Hybrid Epoxy Composites

Abstract: Natural fibers are widely used for reinforcement in polymer composite materials and proved to be effectively replacing synthetic fiber reinforced polymer composites to some extent in applications like domestic, automotive and lower end aerospace parts. The natural fiber reinforced composites are environment friendly, have high strength to weight ratio as well as specific strengths comparable with synthetic glass fiber reinforced composites. In the present work, hybrid epoxy composites were fabricated using cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was observed that fibres treated by microwave irradiation at 385 watts for 8 minutes were entirely damaged and were discarded for they could not be analysed. These variations and differences could be ascribed to the exposure of the inner central lumen of the fibre which may affect the fibre and reduction in fibre diameter due to the loss of weight due to the removal of carbonaceous materials after treatment (Imoisili et al, 2018;Raghu & Goud, 2019) The tenacity (in cN/Tex) of the treated and untreated Calotropis procera bast fibres were also determined and the mean tenacity of the untreated Calotropis procera bast fibres was found to be 37.88 cN/Tex. The highest mean tenacity of 72.06 cN/Tex was recorded for Calotropis procera bast fibres treated in 5% w/v alkali solution for 1 hour while the lowest mean tenacity of 28.79 cN/Tex was recorded for Calotropis procera bast fibres treated in 5% w/v alkali solution for 3 hours.…”
Section: Properties Of the Treated And Untreated Calotropis Bast Fibresmentioning
confidence: 99%
“…It was observed that fibres treated by microwave irradiation at 385 watts for 8 minutes were entirely damaged and were discarded for they could not be analysed. These variations and differences could be ascribed to the exposure of the inner central lumen of the fibre which may affect the fibre and reduction in fibre diameter due to the loss of weight due to the removal of carbonaceous materials after treatment (Imoisili et al, 2018;Raghu & Goud, 2019) The tenacity (in cN/Tex) of the treated and untreated Calotropis procera bast fibres were also determined and the mean tenacity of the untreated Calotropis procera bast fibres was found to be 37.88 cN/Tex. The highest mean tenacity of 72.06 cN/Tex was recorded for Calotropis procera bast fibres treated in 5% w/v alkali solution for 1 hour while the lowest mean tenacity of 28.79 cN/Tex was recorded for Calotropis procera bast fibres treated in 5% w/v alkali solution for 3 hours.…”
Section: Properties Of the Treated And Untreated Calotropis Bast Fibresmentioning
confidence: 99%
“…The same has been studied through Taguchi's L9 orthogonal array method. Raghu et al [ 36 ] focused on wear performance evaluation of calotropis procera/glass fiber reinforced hybrid composites, where the varying percentage (5% of natural fiber), 15% and 20% of glass fiber in hybrid composite showed less wear rate.…”
Section: Introductionmentioning
confidence: 99%